Strategi Komunikasi Pembangunan Pemerintah Kabupaten Bojonegoro dalam Menerapkan Nawacita dan Tujuan Pembangunan Berkelanjutan - Ramadhani, Rizky Wulan; Prihantoro, Edy - (Jurnal Komunikasi Pembangunan, 2020)
Sustainable Development Goals (SDGs) is an agenda declared by United Nations on 2015 that should be achieved on 2030. Nawacita is a series of programs proposed by Jokowi-JK during 2014-2019 period which includes ways to achieved SDGs in Indonesia. The aim of this research is to know the development communication strategies used by Bojonegoro District Government on communicating Nawacita and SDGs. This research uses qualitative methodology by doing interview and documentation. Key informant on this research is Kang Yoto, Regent of Bojonegoro on 2008-2018 period. The result of this research is that Bojonegoro District Government uses strategies based on media used, instructional design strategy, marketing strategy, and participatory strategy. Strategies used are effective to persuade Bojonegoro people to support the achievement of SDGs and to inform public about SDGs. These strategies can be used by another local government by considering condition of their people.